Alcohol Use and Activity Limitations in Gout Patients. (November 2016) - Harding, Mariann
Abstract : BACKGROUND: Few studies have evaluated whether patients with a diagnosis of gout adhere to alcohol use recommendations and the relationship between adherence and activity limitations. PURPOSE: The purpose of this study was to determine adherence to American College of Rheumatology (ACR) alcohol use recommendations and evaluate the relationship between alcohol use and activity limitations in persons with gout. METHOD: A secondary analysis was performed with a sample of 298 persons with gout from the 2008 National Health Interview Survey. RESULTS: In all, 22.8% of persons with gout were nonadherent to alcohol use recommendations. Males, those aged 41–60 years, and those not receiving healthcare for joint symptoms were most likely to be nonadherent. In all, 39.9% reported that joint symptoms interfered with activity in the preceding 30 days. Those who were adherent were more likely to report limitations (χ 2 = 6.788, p = .03). CONCLUSIONS: To promote optimal patient outcomes, more attention needs to be devoted to individualized patient education and self-management interventions that follow ACR recommendations.